Intra-industry trade, product fragmentation and technological capability development in Thai automotive industry. Issue 1 (2nd January 2016) - Intarakumnerd, Patarapong; Techakanont, Kriengkrai
Abstract : Thailand's automotive industry has evolved from a small import-substituting industry to a vibrant exporting one. It has contributed significantly and increasingly to the economy and intra-industry trade in Southeast Asia. The country also has experienced 'qualitative' change from simple production to technologically sophisticated activities. The evidence amassed illustrates that firm strategy and collaboration with other actors in the national innovation system were the most important drivers of technological upgrading in the industry. Local automotive part suppliers in particular had to become 'active' learners by collaborating with other partners beyond their own multinational buyers to compete in export markets.